Keberkesanan Komunikasi dalam Organisasi ke Arah Kejayaan Sesebuah Projek Pembinaan - Nasarudin Fitri, Nur Ilyanajwa; Abd Rahim, Mohd Hilmi Izwan; Shareh Musa, Sharifah Meryam; Kasim, Narimah (Research in Management of Technology and Business, 2023)
Effective communication is very important in the implementation of a construction project. Construction projects require cooperation and earnest involvement from all parties to ensure that the project can be successful according to the set criteria. The issue of ineffective communication contributes to the problem of delays and cost overruns that are common in construction projects. Therefore, the purpose of this study is to examine the effectiveness of communication in the organization towards the success of a construction project. This study focuses on two (2) research objectives which are to examine the communication challenges that hinder the success of the project and to identify recommendations to overcome effective communication problems in the construction industry. This study was conducted using literature review and quantitative methods by distributing questionnaires to Grade 7 (G7) contractors. This study was conducted around the area of the state of Johor. A total of 248 G7 contractors were selected from a total population of 710 contractors to be respondents for this study. Research data obtained from the distribution of questionnaires were analysed using the Statistical Package for Social Science (SPSS) software. Descriptive statistical analysis including frequency distribution and mean score is required to determine the challenges and steps to overcome communication effectiveness problems in the construction industry. The results of this study are the challenges of effective communication that prevent the success of a project can be overcome well. In addition, the construction industry is expected to be able to improve measures to overcome the problem of communication effectiveness according to the current technology trend. Overall, the perception of Grade 7 contractors around the state of Johor towards the effectiveness of communication in the organization towards the success of a construction project shows a high agreement and response to the matters presented through the questionnaire.